Detection of plasma anti-lipopolysaccharide (LPS) antibodies against enterohemorrhagic Escherichia coli (EHEC) in asymptomatic kindergarten teachers from Buenos Aires province - Fernández Brando, Romina Jimena (2023)
In Argentina, hemolytic uremic syndrome (HUS) caused by EHEC has the highest incidence in the world. EHEC infection has an endemo-epidemic behavior, causing 20---30% of acutebloody diarrhea syndrome in children under 5 years old. In the period 2016---2020, 272 new casesper year were notified to the National Health Surveillance System. Multiple factors are responsible for HUS incidence in Argentina including person-to-person transmission. In order to detectpossible EHEC carriers, we carried out a preliminary study of the frequency of kindergartenteachers with anti-LPS antibodies against the most prevalent EHEC serotypes in Argentina. Weanalyzed 61 kindergarten teachers from 26 institutions from José C. Paz district, located in thesuburban area of Buenos Aires province, Argentina. Fifty-one percent of the plasma sampleshad antibodies against O157, O145, O121 and O103 LPS: 6.4% of the positive samples had IgMisotype (n = 2), 61.3% IgG isotype (n = 19) and 32.3% IgM and IgG (n = 10). Given that antibodies against LPS antigens are usually short-lived specific IgM detection may indicate a recent infection. In addition, the high percentage of positive samples may indicate a frequent exposureto EHEC strains in the cohort studied, as well as the existence of a large non-symptomaticpopulation of adults carrying pathogenic strains that could contribute to the endemic behaviorthrough person-to-person transmission. The improvement of continuous educational programsin kindergarten institutions could be a mandatory measure to reduce HUS cases not only inArgentina but also globally.